Serum Trace Elements and Antioxidant Vitamins among Male Patients with Prostate Disorders in the Delta Region of Nigeria - Bhaguetai Joseph Aghawegbehe; Adedeji David Atere; David Bolaji Akinbo; Olumide Faith Ajani; Raphael Usiosefe Erhunmwunse (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Prostate cancer remains the commonest form of cancer among Nigerian males, constituting 13.3% of all male cancers encountered in this region. Trace elements and antioxidant vitamins may be of epidemiological significance in the early prediction and treatment of prostate complications. The study aimed to explore the serum trace elements, antioxidant vitamins concentration and serum prostate specific antigen (PSA) among male with prostate disorders in the delta region of Nigeria.Methods: Blood specimens were collected from males with symptoms of prostatitis (n=70), benign prostatic hyperplasia (BPH; n=60) and prostate cancer (PCa; n=70), alongside with apparently healthy male subjects (n=60). The levels of trace elements and antioxidant vitamins were evaluated. Fluorescence immunoassay technique was used to assess the expression of PSA. Results: Compared with the controls, PCa patients had a significantly increased level of vitamin A (p<0.05), however, no significant differences in the serum levels of trace elements and antioxidant vitamins between subjects with prostate disorders and control group (p>0.05). Interestingly, there was a significant positive correlation between prostate specific antigen, trace elements and vitamins in BPH group (p<0.05).Conclusions: Prostate disorders such as prostatitis, BPH and PCa may be associated with elevated levels of PSA, but, does not affect the circulating expression of some serum trace elements and antioxidant vitamins.